Pengaruh Kebijakan Pemerintah terhadap Produksi dan Pendapatan Usahatani Padi di Wilayah Bosowasipilu Sulawesi Selatan - Supriady Rusli (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The study aimed to find out (1) an opportunity for the improvement of rice production which has not been utilized optimally yet; (2) the farmer’s planting area; (3) agribusiness activities starting from farming, marketing and processing at the first stage in obtaining added value and absorption of labors.The result of the study indicate that the opportunity owned by South Sulawesi when it is used appropriately will provide greater profit compared to import rice, so that it will encourage the improvement of income and the absorption of labors. The farmers have not been able to maximize their income yet due to inefficiency in the utilization of production factors and are irresponsive to the change of rice price.Keywords: Production of Rice, farmers income, Bosowasipilu, South Sulawesi.